Mildew-proof and antibacterial nano water-based paint and preparation process thereof
By combining components such as composite nanoparticles and modified metal particles, an anti-mildew and antibacterial nano water-based coating is prepared, which solves the problems of insufficient anti-mildew and antibacterial ability and durability of existing water-based coatings, and achieves the broad-spectrum antibacterial and yellowing resistance effects of the coating.
Patent Information
- Application Number
- CN202511088027.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-05
- Publication Date
- 2025-10-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing water-based coatings have limited mildew and antibacterial capabilities and durability, and poor yellowing resistance, which limits the expansion of their application range.
A combination of composite nanoparticles, modified metal particles, graphene oxide and light stabilizers is used to prepare anti-mildew and antibacterial nano water-based coatings through ultrasonic dispersion, stirring and high shear processes to form a multiple antibacterial system and enhance the interfacial compatibility and photocatalytic ability of the coating.
It significantly improves the antibacterial and anti-mildew ability, durability and yellowing resistance of the coating, enhances the stability and adhesion of the coating, and expands the scope of application.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of paint, in particular to a mildew-proof and antibacterial type nano water-based paint and a preparation process thereof. BACKGROUND
[0002] The water-based paint is a paint with water as a solvent or a dispersion medium, and its main components are water-based resin (such as acrylic resin, polyurethane resin, epoxy resin, etc.), pigment and filler, additive and water. It has the characteristics of environmental protection, low volatile organic compounds, safety, etc., and is widely used in the fields of building, industry, wood, metal, etc. Among them, the water-based polyurethane resin paint is an environmentally friendly paint with polyurethane resin as the main film-forming material and water as the dispersion medium. It combines the high performance (such as high wear resistance, flexibility, chemical resistance) of solvent-based polyurethane paint and the low volatile organic compounds emission, safety and environmental protection of water-based paint.
[0003] Based on the above characteristics, the water-based polyurethane resin paint is widely used in the fields of building, furniture, automobile, leather, industrial protection, etc. However, its own problems such as limited mildew-proof and antibacterial ability, limited durability, poor yellowing resistance, etc. greatly limit the further expansion of the application range. SUMMARY
[0004] The purpose of the present application is to provide a mildew-proof and antibacterial type nano water-based paint and a preparation process thereof, which solves the following technical problems: The existing water-based paint still has the problems of limited mildew-proof and antibacterial ability, limited mildew-proof and antibacterial durability, and poor yellowing resistance.
[0005] The purpose of the present application can be achieved by the following technical solutions: A mildew-proof and antibacterial type nano water-based paint, comprising the following raw materials by mass: deionized water 12-14 parts, composite antibacterial agent 1.8-2.1 parts, wetting dispersant 0.8-0.9 parts, 2-hydroxy-4-n-octyloxybenzophenone 0.1-0.12 parts, water-based polyurethane resin 55-60 parts, alcohol ester-12 1.5-1.8 parts.
[0006] Preferably, the preparation method of the composite antibacterial agent is as follows: The composite nanoparticles are dissolved in deionized water and ultrasonically dispersed for 30-35 min, then the modified metal particle dispersion liquid is added dropwise while stirring, stirred for 1.8-2 h, then the silver nitrate solution is added dropwise, then stirred in the dark for 1.8-2 h, then centrifuged for 8-10 min, the precipitate is redissolved in another portion of deionized water, then the light stabilizer 770 ethanol solution is added, finally the graphene oxide dispersion liquid is added dropwise and the pH is adjusted to 7.7-7.9, then stirred for 10-12 h, then filtered and dried to obtain the composite antibacterial agent.
[0007] Preferably, the use amount ratio of the composite nanoparticles, deionized water, modified metal particle dispersion solution, silver nitrate solution, another portion of deionized water, light stabilizer 770 ethanol solution, and graphene oxide dispersion solution is 1.0-1.2 g: 100-120 mL: 50-60 mL: 10-12 mL: 50-60 mL: 5-6 mL: 50-60 mL. The concentration of the silver nitrate solution is 0.08-0.1 mol / L. The mass fraction of the light stabilizer 770 ethanol solution is 4%.
[0008] Preferably, the preparation method of the composite nanoparticles is as follows: Chitosan is added to an acetic acid-sodium acetate buffer solution and stirred at 40-45℃ for 2-3h, then dopamine hydrochloride, ascorbic acid, and ammonium persulfate are added and stirred in the dark for 24-25h, the precipitate is filtered and washed after dialysis for 48-50h using a dialysis membrane, and the precipitate is freeze-dried after centrifugation to obtain the composite nanoparticles.
[0009] Preferably, the use amount ratio of the acetic acid-sodium acetate buffer solution, chitosan, dopamine hydrochloride, ascorbic acid, and ammonium persulfate is 100-120 mL: 2-2.4 g: 1.8-2 g: 0.1-0.12 g: 2.2-2.4 g. The concentration of the acetic acid-sodium acetate buffer solution is 0.5 mol / L, and the pH is 5.0. The molecular weight cut-off of the dialysis membrane is 10 kDa. The pore size of the filter paper during filtration is 0.22 μm. The temperature during freeze-drying is -55--50℃, the pressure is 0.08-0.1 mbar, and the time is 3.8-4h.
[0010] Preferably, the preparation method of the modified metal particle dispersion solution is as follows: A1: Cobalt nitrate hexahydrate is dissolved in deionized water, then tungsten phosphate precursor salt is added, and the solution is heated to 80-85℃ while stirring, then stirring is continued for 80-90 min, the solution is cooled to 25-30℃, potassium chloride is added and stirred for 15-20 min, the precipitate is filtered and washed, the precipitate is dissolved in deionized water at 80-90℃, the solution is cooled to 3-5℃ for 12-15h, then the precipitate is filtered, and finally the precipitate is vacuum dried to obtain the modified metal particles. A2: The modified metal particles are added to deionized water, ultrasonic dispersion is performed for 20-30 min, then the pH is adjusted to 7.0 using ammonia water, high-pressure homogenization is performed, then silane coupling agent KH550 is added and stirred at 58-60℃ for 25-30 min to obtain the modified metal particle dispersion solution.
[0011] Preferably, the usage ratio of the cobalt nitrate hexahydrate, deionized water, tungsten phosphate precursor salt, potassium chloride, and deionized water at 80-90° C. in A1 is 0.41-0.49 g: 15-18 mL: 2.0-2.4 g: 5-6 g: 10-15 mL; The tungsten phosphate precursor salt in A1 is any one of sodium phosphotungstate and ammonium phosphotungstate; The usage ratio of deionized water, modified metal particles, and silane coupling agent KH550 in A2 is 50-60 mL: 0.5-0.6 g: 0.1-0.12 g; The pressure during the high-pressure homogenization in A2 is 110-120 MPa, and the number of high-pressure homogenization times is 3-5 times.
[0012] Preferably, the preparation method of the graphene oxide dispersion is as follows: Graphene oxide and dopamine are added to deionized water and ultrasonic treatment is performed for 25-30 minutes. Then, polyacrylic acid and nano-titanium dioxide are added and ultrasonic treatment is performed for 2-2.5 hours to obtain a graphene oxide dispersion.
[0013] Preferably, the usage ratio of the deionized water, graphene oxide, dopamine, polyacrylic acid and nano-titanium dioxide is 50-60 mL: 0.5-0.6 g: 0.03-0.05 g: 0.05-0.06 g: 0.2-0.24 g.
[0014] A preparation process of a mildew-proof and antibacterial nano water-based coating comprises the following steps: Add a composite antibacterial agent, a wetting dispersant, and 2-hydroxy-4-n-octyloxybenzophenone to deionized water and perform ultrasonic dispersion for 15-20 minutes. Then, add a water-based polyurethane resin dropwise while stirring. Repeat high-speed shearing 3-4 times and add alcohol ester-12. Then, adjust the pH to 8.1-8.3 with ammonia water and perform high-speed shearing again to obtain a mildew-proof and antibacterial nano water-based coating. The rotation speed during the high-speed shearing is 11000-12000 r / min, and the duration is 6-8 minutes.
[0015] As a further embodiment of the present invention.
[0016] Beneficial effects of the present invention: The present invention provides a mildew-proof and antibacterial nano water-based paint and a preparation process thereof. The present invention effectively improves the yellowing resistance, antibacterial and mildew-proof capabilities and long-term effectiveness of the water-based paint through the following method.
[0017] (1) The chitosan in the composite nanoparticles contains a large number of amino groups, can be adsorbed on the surface of microorganisms, destroy the cell membrane permeability, can chelate metal ions, inhibit enzyme activity, can regulate microbial metabolic pathways, directly endow the coating with broad-spectrum antibacterial ability, and the biocompatibility of chitosan makes it suitable for environmentally friendly coatings. The ortho-phenol group of dopamine is easy to oxidize into quinone structure, which can damage microorganisms through oxidative stress reaction; the amino group on the surface of the composite nanoparticles can also adsorb silver ions in the subsequent added silver nitrate, and through the reduction reaction, nano-silver particles are formed, forming a multiple antibacterial system of 'chitosan+dopamine+nanosilver', which significantly improves the mildew resistance, antibacterial ability and durability of the coating. Chitosan can also crosslink with ammonium persulfate to form a polymer network with dopamine, providing physical support for the nanoparticles while combining with subsequent modified metal particles, graphene oxide and other components through hydrogen bonding or electrostatic interaction, enhancing the interfacial compatibility of the composite material, avoiding aggregation during dispersion, reducing pore defects, thereby enhancing water erosion resistance and mechanical strength. Ascorbic acid in the composite nanoparticles can adjust the degree of oxidative polymerization of dopamine, control the particle size of the nanoparticles, and also can stabilize the free radicals in the chitosan-dopamine network, inhibit side reactions, ensure uniform particle morphology, avoid large particle sedimentation, and improve the stability of the coating.
[0018] (2) During the preparation of the modified metal particle dispersion liquid, KH550 can significantly improve the interfacial compatibility of inorganic modified metal particles and organic matrix, reduce filler aggregation, make it uniformly dispersed in the coating, avoid coating defects caused by metal particle aggregation, thereby enhancing the overall density and stability of the coating, hindering the penetration of water molecules, reducing the damage of hydrolysis reaction to the coating, and further improving the aging resistance; also can form a stronger interface between inorganic fillers and organic resins through'molecular bridge' effect, improve the adhesion, impact resistance and flexibility of the coating, and indirectly improve the aging resistance; the siloxane coating layer formed on the surface of the metal particles can act as a physical barrier to reduce the direct contact of metal particles with water, oxygen and corrosive media, and inhibit the migration or oxidation of metal ions. In addition, the presence of amino groups may neutralize the acidic groups in the system, reduce the chemical active sites inside the coating, and delay the yellowing and aging caused by photo-oxidation or thermal-oxidation reaction.
[0019] (3) The graphene oxide dispersion liquid can load more antibacterial components through physical adsorption or chemical bonding, and after mixing with the composite antibacterial agent, a "graphene oxide-metal particle-silver ion" composite antibacterial network can be formed, which can destroy the microbial cell membrane through contact or slow-release effect; graphene oxide can improve the efficiency of photocatalytic production of active oxygen through the separation of photo-generated electron-hole pairs, strengthen the antibacterial ability, and its sheet structure can pierce the bacterial cell wall, enhance the contact sterilization effect, and it can also form hydrogen bonds or ionic bonds with the amino groups of chitosan, reduce the loss of antibacterial components through interface anchoring effect, and prolong the antibacterial time effect. The added dopamine can form a polydopamine layer to coat the surface of graphene oxide through oxidation self-polymerization, and the adhesive groups of polydopamine can enhance the interfacial bonding force between graphene oxide and the resin matrix and the substrate, reducing the risk of coating cracking or peeling. The combination of graphene oxide and nano titanium dioxide can form a "ultraviolet filtering-photocatalytic degradation" synergistic system, reducing the yellowing and embrittlement of the coating caused by photooxidation reaction. The added polyacrylic acid can prevent particle agglomeration through electrostatic repulsion and steric hindrance effect, hinder direct contact between particles, and ensure the uniformity and stability of the final coating; the carboxyl groups of polyacrylic acid can react with the hydroxyl and epoxy groups on the surface of graphene oxide, enhancing the anchoring effect of the polymer chain and graphene, and can also form chemical bonds with the hydroxyl groups on the surface of nano titanium dioxide, improving the interfacial bonding between inorganic particles and organic matrix, enhancing the mechanical strength and durability of the coating, reducing the loss of antibacterial components caused by interface separation, and prolonging the persistence of the mildew-resistant and antibacterial effect; polyacrylic acid can also inhibit the excessive growth of crystals, thereby controlling the particle size of nano titanium dioxide, keeping it small in size, increasing the specific surface area, enhancing the photocatalytic activity, enhancing the inhibition effect on mold, and improving the antibacterial spectrum of the composite system; affecting the stacking of graphene oxide sheets, keeping them in a single dispersed or few-layer state, and enhancing their adsorption capacity for microorganisms.
[0020] (4)The 2-hydroxy-4-n-octyloxybenzophenone added in the present application can convert light energy into harmless heat energy release, avoid the oxidation degradation and chain scission of the polymer in the coating caused by ultraviolet light, thereby significantly improving the aging resistance of the coating, delaying the phenomena such as yellowing, powdering and cracking; it can also form a complex system with light stabilizer 770 to cover a wider range of ultraviolet wavelengths, and further enhance the yellowing resistance through mechanisms such as capturing free radicals and quenching excited state molecules. The alcohol ester-12 added in the present application can penetrate between the particles of the waterborne polyurethane resin, reduce the energy required for particle agglomeration, help the coating to form a continuous and dense paint film at low temperature, avoid the problems such as coating cracking and poor adhesion caused by incomplete film formation, and promote the diffusion and entanglement of resin molecular chains, improve the hardness, flexibility and impact resistance of the paint film, and also improve the leveling and wetting properties of the coating, reduce defects such as brush marks and orange peel, make the coating surface smoother and more uniform, and improve the water permeability resistance.
[0021] Therefore, the water-based paint prepared by the present application has excellent adhesion, impact resistance, yellowing resistance, antibacterial and mildew resistance and long-acting, and has a more extensive application prospect. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present application will be described below in a clear and complete manner. Obviously, the described embodiments are only part of the embodiments of the present application, not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.
[0023] Unless otherwise specified, the information of some raw materials used in the following examples and comparative examples of the present application is as follows: Chitosan was purchased from Shanghai Aldrin Biochemical Technology Co., Ltd., item number: C105799; sodium dodecatungstate was purchased from Shanghai Aldrin Biochemical Technology Co., Ltd., item number: S104082; ammonium dodecatungstate was purchased from Hubei Jusheng Technology Co., Ltd., CAS: 12704-02-8; graphene oxide was purchased from Shanghai Aldrin Biochemical Technology Co., Ltd., item number: G139803; polyacrylic acid was purchased from Shanghai Jiachen Chemical Co., Ltd., CAS: 9007-20-9; nano-titanium dioxide was rutile type, purchased from Nanjing Bemoda Biological Technology Co., Ltd., CAS: 13463-67-7; 2-hydroxy-4-n-octyloxybenzophenone was purchased from Shanghai Yuanye Bio-technology Co., Ltd., CAS: 1843-05-6; light stabilizer 770 was purchased from Wuhan Xinxinjiali Biological Technology Co., Ltd., CAS: 52827-07-9; wetting and dispersing agent BYK-190 was purchased from Forshman Technology (Beijing) Co., Ltd., item number: 9709009; water-based polyurethane resin was Bayhydrol UH 2593 / 1, purchased from Shanghai Yinhe Chemical Co., Ltd.; alcohol ester-12 was purchased from Wuhan Xinxinjiali Biological Technology Co., Ltd., CAS: 25265-77-2.
[0024] Example 1: A preparation process of a mildew-resistant and antibacterial type nano water-based paint is as follows: S1: 2 g of chitosan was added in 100 mL of 0.5 mol / L acetic acid-sodium acetate buffer solution with pH of 5.0 and stirred at 560 r / min for 2 h at 40℃, then 1.8 g of dopamine hydrochloride, 0.1 g of ascorbic acid and 2.2 g of ammonium persulfate were added and stirred at 650 r / min for 24 h in the dark, then the dialysis membrane with a molecular weight cut-off of 10 kDa was used for dialysis for 48 h, then 0.22 μm filter paper was used for filtration, then the precipitate was washed with deionized water for 2 times, then centrifuged at 3800 r / min for 5 min, then the precipitate was freeze-dried at -55℃, 0.08 mbar for 3.8 h, to obtain composite nanoparticles; S2: 0.41 g of cobalt nitrate hexahydrate was dissolved in 15 mL of deionized water, then 2 g of phosphorus dodecatungstate sodium was added and stirred at 800 r / min, then heated to 80℃ at a rate of 1.5℃ / min, then continued to stir at 80℃ for 80 min, then cooled to 25℃, then 5 g of potassium chloride was added and stirred at 800 r / min for 15 min, then filtered, then the precipitate was washed with 50% ethanol aqueous solution by ultrasonic washing at a power of 280 W for 5 min, then the precipitate was dissolved in 10 mL of deionized water at 80℃, then cooled at 3℃ for 12 h, then filtered, then the precipitate was vacuum dried at 78℃ for 2 h, to obtain modified metal particles; S3: 0.5 g modified metal particles were added into 50 mL deionized water, ultrasonic dispersion was carried out at a power of 450 W for 20 min, then the pH was adjusted to 7.0 with ammonia water, and then 3 times of 110 MPa high pressure homogenization was carried out, finally 0.1 g silane coupling agent KH550 was added and stirred at 58℃ for 25 min, to obtain a modified metal particle dispersion liquid; S4: 0.5 g graphene oxide and 0.03 g dopamine were added into 50 mL deionized water, and ultrasonic treatment was carried out at a power of 450 W for 25 min, then 0.05 g polyacrylic acid and 0.2 g nano titanium dioxide were added and ultrasonic treatment was carried out at a power of 450 W for 2 h, to obtain a graphene oxide dispersion liquid; S5: 1.0 g composite nanoparticles were dissolved in 100 mL deionized water, ultrasonic dispersion was carried out at a power of 180 W for 30 min, then 50 mL modified metal particle dispersion liquid was added dropwise at a rate of 0.8 mL / min while stirring at 750 r / min, stirring was carried out at 750 r / min for 1.8 h, then 10 mL silver nitrate solution with a concentration of 0.08 mol / L was added dropwise at a rate of 0.3 mL / min, then stirring was carried out at 550 r / min in the dark for 1.8 h, then centrifugation was carried out at 7800 r / min for 8 min, the precipitate was redissolved in 50 mL deionized water, then 5 mL light stabilizer 770 ethanol solution with a mass fraction of 4% was added, finally 50 mL graphene oxide dispersion liquid was added dropwise at a rate of 0.8 mL / min and the pH was adjusted to 7.7 with triethanolamine, stirring was carried out at 450 r / min for 10 h, then filtration and drying treatment were carried out, to obtain a composite antibacterial agent; S6: 1.8 g composite antibacterial agent, 0.8 g wet dispersant BYK-190 and 0.1 g 2-hydroxy-4-n-octyloxybenzophenone were added into 12 mL deionized water, ultrasonic dispersion was carried out at a power of 200 W for 15 min, then 55 g waterborne polyurethane resin was added dropwise at a rate of 1 g / min while stirring at 580 r / min, shearing was carried out at 11000 r / min for 6 min and 0.5 g alcohol ester-12 was added, then the pH was adjusted to 8.1 with ammonia water, shearing was carried out at 11000 r / min for 6 min again, to obtain a mildew-resistant and antibacterial type nano waterborne coating.
[0025] Example 2: The preparation process of a mildew-resistant and antibacterial type nano waterborne coating is as follows: S1: 2.2 g of chitosan was added into 110 mL of acetic acid-sodium acetate buffer solution with a concentration of 0.5 mol / L at pH 5.0 and stirred at 580 r / min for 2.5 h at 43 °C, then 1.9 g of dopamine hydrochloride, 0.11 g of ascorbic acid and 2.3 g of ammonium persulfate were added and stirred at 680 r / min for 24.5 h in the dark, then dialyzed for 49 h at room temperature using a dialysis membrane with a molecular weight cut-off of 10 kDa, filtered with 0.22 μm filter paper, and the precipitate was washed with deionized water for 3 times, centrifuged at 3900 r / min for 5.5 min, then the precipitate was freeze-dried at -53 °C, 0.09 mbar for 3.9 h, to obtain the composite nanoparticles; S2: 0.45 g of cobalt nitrate hexahydrate was dissolved in 17 mL of deionized water, then 2.2 g of sodium phosphotungstate dodecahydrate was added and heated to 83 °C at 2 °C / min while stirring at 850 r / min, continued to stir at 83 °C for 85 min, then cooled to 28 °C, then 5.5 g of potassium chloride was added and stirred at 850 r / min for 18 min, then filtered, washed with 53% ethanol aqueous solution for 2 times for 5.5 min with a power of 290 W, then the precipitate was dissolved in 13 mL of deionized water at 85 °C, cooled to 4 °C for 14 h, then filtered and the precipitate was vacuum dried at 79 °C for 2.3 h, to obtain the modified metal particles; S3: 0.55 g of modified metal particles was added into 55 mL of deionized water, ultrasonically dispersed for 25 min with a power of 480 W, then the pH was adjusted to 7.0 with ammonia water, then subjected to 4 times of high-pressure homogenization at 115 MPa, finally 0.11 g of silane coupling agent KH550 was added and stirred at 59 °C for 28 min, to obtain a modified metal particle dispersion; S4: 0.55 g of graphene oxide, 0.04 g of dopamine and 0.055 g of polyacrylic acid were added into 55 mL of deionized water and ultrasonically treated for 28 min with a power of 480 W, then 0.22 g of nano-titanium dioxide was added and ultrasonically treated for 2.3 h with a power of 480 W, to obtain a graphene oxide dispersion; S5: 1.1 g of the composite nanoparticles were dissolved in 110 mL of deionized water, ultrasonic dispersion was performed at a power of 190 W for 33 min, then 55 mL of the modified metal particle dispersion liquid was added dropwise at a rate of 0.9 mL / min while stirring at 780 r / min, stirring was performed at 780 r / min for 1.9 h, then 11 mL of a silver nitrate solution with a concentration of 0.09 mol / L was added dropwise at a rate of 0.4 mL / min, then stirring was performed at 580 r / min in the dark for 1.9 h, centrifugation was performed at 7900 r / min for 9 min, the precipitate was redissolved in 55 mL of deionized water, then 5.5 mL of a light stabilizer 770 ethanol solution with a mass fraction of 4% was added, then 55 mL of the graphene oxide dispersion liquid was added dropwise at a rate of 0.9 mL / min and the pH was adjusted to 7.8 with triethanolamine, stirring was performed at 460 r / min for 11 h, then filtration and drying treatment were performed, and a composite antibacterial agent was obtained; S6: 1.95 g of the composite antibacterial agent, 0.85 g of the wet dispersant BYK-190, and 0.11 g of 2-hydroxy-4-n-octyloxybenzophenone were added to 13 mL of deionized water, ultrasonic dispersion was performed at a power of 200 W for 18 min, then 58 g of the waterborne polyurethane resin was added dropwise at a rate of 1.5 g / min while stirring at 590 r / min, shearing was performed at 11500 r / min for 7 min and 0.55 g of alcohol ester-12 was added, then the pH was adjusted to 8.2 with ammonia water, shearing was performed at 11500 r / min for 7 min again, and a mildew-resistant and antibacterial type nano waterborne coating was obtained.
[0026] Example 3: A mildew-resistant and antibacterial type nano waterborne coating was prepared according to the following process: S1: 2.4 g of chitosan was added to 120 mL of an acetic acid-sodium acetate buffer with a pH of 5.0 and a concentration of 0.5 mol / L, stirring was performed at 600 r / min at 45 °C for 3 h, then 2 g of dopamine hydrochloride, 0.12 g of ascorbic acid, and 2.4 g of ammonium persulfate were added, stirring was performed at 700 r / min in the dark for 25 h, dialysis was performed at room temperature for 50 h using a dialysis membrane with a molecular weight cut-off of 10 kDa, filtration was performed using a 0.22 μm filter paper, the precipitate was washed with deionized water four times, centrifugation was performed at 4000 r / min for 6 min, then the precipitate was freeze-dried at -50 °C and 0.1 mbar for 4 h, and composite nanoparticles were obtained; S2: 0.49 g of cobalt nitrate hexahydrate was dissolved in 18 mL of deionized water, then 2.4 g of ammonium phosphotungstate was added and heated to 85°C at 2.5°C / min while stirring at 900 r / min, after stirring at 85°C for 90 min, it was cooled to 30°C, then 6 g of potassium chloride was added and stirred at 900 r / min for 20 min, then filtered, washed with 55% ethanol aqueous solution for 3 times for 5-6 min with power of 300 W, then the precipitate was dissolved in 15 mL of deionized water at 90°C, cooled at 5°C for 12-15 h, then filtered and the precipitate was vacuum dried at 80°C for 2.5 h to obtain modified metal particles; S3: 0.6 g of modified metal particles was added in 60 mL of deionized water, ultrasonic dispersed for 30 min with power of 500 W, then the pH was adjusted to 7.0 with ammonia water, then homogenized for 5 times at 120 MPa, finally 0.12 g of silane coupling agent KH550 was added and stirred at 60°C for 30 min to obtain modified metal particle dispersion; S4: 0.6 g of graphene oxide, 0.05 g of dopamine was added in 60 mL of deionized water and ultrasonic treated for 30 min with power of 500 W, then 0.06 g of polyacrylic acid, 0.24 g of nano titanium dioxide was added and ultrasonic treated for 2.5 h with power of 500 W to obtain graphene oxide dispersion; S5: 1.2 g of composite nanoparticles was dissolved in 120 mL of deionized water and ultrasonic dispersed for 35 min with power of 200 W, then 60 mL of modified metal particle dispersion was added dropwise at 1 mL / min while stirring at 800 r / min, stirred at 800 r / min for 2 h, then 12 mL of silver nitrate solution with concentration of 0.1 mol / L was added dropwise at 0.5 mL / min, then stirred at 600 r / min in dark for 2 h, then centrifuged at 8000 r / min for 10 min, the precipitate was redissolved in 60 mL of deionized water, then 6 mL of light stabilizer 770 ethanol solution with mass fraction of 4% was added, finally 60 mL of graphene oxide dispersion was added dropwise at 1 mL / min and the pH was adjusted to 7.9 with triethanolamine, stirred at 500 r / min for 12 h, then filtered and dried to obtain composite antibacterial agent; S6: 2.1 g of composite antibacterial agent, 0.9 g of wetting dispersant BYK-190, 0.12 g of 2-hydroxy-4-n-octyloxybenzophenone was added in 14 mL of deionized water and ultrasonic dispersed for 20 min with power of 200 W, then 60 g of waterborne polyurethane resin was added dropwise at 2 g / min while stirring at 600 r / min, repeated for 4 times with shearing at 12000 r / min for 8 min and 0.6 g of alcohol ester-12 was added, then the pH was adjusted to 8.3 with ammonia water, then sheared at 12000 r / min for 8 min to obtain mildew-resistant antibacterial type nano waterborne paint.
[0027] Comparative Example 1: The comparative example is compared with Example 1 only without adding "0.1 g ascorbic acid" in the preparation process of the composite nanoparticles in S1, and the rest of the steps and parameters are the same. The comparative example will not be repeated here. Finally, the mildew-resistant and antibacterial type of nano water-based paint is obtained.
[0028] Comparative Example 2: The comparative example is compared with Example 1 only without adding "30.1 g silane coupling agent KH550" in the preparation process of the modified metal particle dispersion liquid in S2, and the rest of the steps and parameters are the same. The comparative example will not be repeated here. Finally, the mildew-resistant and antibacterial type of nano water-based paint is obtained.
[0029] Comparative Example 3: The comparative example is compared with Example 1 only without adding "0.03 g dopamine" in the preparation process of the graphene oxide dispersion liquid in S4, and the rest of the steps and parameters are the same. The comparative example will not be repeated here. Finally, the mildew-resistant and antibacterial type of nano water-based paint is obtained.
[0030] Comparative Example 4: The comparative example is compared with Example 1 only without adding "0.05 g polyacrylic acid" in the preparation process of the graphene oxide dispersion liquid in S4, and the rest of the steps and parameters are the same. The comparative example will not be repeated here. Finally, the mildew-resistant and antibacterial type of nano water-based paint is obtained.
[0031] Comparative Example 5: The comparative example is compared with Example 1 only without adding "0.2 g nano titanium dioxide" in the preparation process of the graphene oxide dispersion liquid in S4, and the rest of the steps and parameters are the same. The comparative example will not be repeated here. Finally, the mildew-resistant and antibacterial type of nano water-based paint is obtained.
[0032] Comparative Example 6: The comparative example is compared with Example 1 only without adding "10 mL of 0.08 mol / L silver nitrate solution" in the preparation process of the composite antibacterial agent in S5, and the rest of the steps and parameters are the same. The comparative example will not be repeated here. Finally, the mildew-resistant and antibacterial type of nano water-based paint is obtained.
[0033] Comparative Example 7: The comparative example is compared with Example 1 only without adding "50 mL of graphene oxide dispersion liquid" in the preparation process of the composite antibacterial agent in S5, and the rest of the steps and parameters are the same. The comparative example will not be repeated here. Finally, the mildew-resistant and antibacterial type of nano water-based paint is obtained.
[0034] Comparative Example 8: The comparative example is compared with example 1 only without adding “0.1 g of 2-hydroxy-4-n-octyloxybenzophenone” in the preparation process of the mildew-resistant and antibacterial type nano water-based paint of S6, and the rest of the steps and parameters are the same. The comparative example will not be repeated here. Finally, the mildew-resistant and antibacterial type nano water-based paint is obtained.
[0035] Comparative example 9: The comparative example is compared with example 1 only without adding “1.5 g of alcohol ester-12” in the preparation process of the mildew-resistant and antibacterial type nano water-based paint of S6, and the rest of the steps and parameters are the same. The comparative example will not be repeated here. Finally, the mildew-resistant and antibacterial type nano water-based paint is obtained.
[0036] Performance detection: Spray the mildew-resistant and antibacterial type nano water-based paint with a thickness of 90-100 μm on a 100 mm x 100 mm rust-free, oil-free, clean and dry steel plate. Then dry at 25°C for 1.5h, and then dry at 65°C for 3h, to obtain the test sample plate.
[0037] Determination of antibacterial ability and long-term effectiveness: According to the standard GB / T 21866-2008 “Determination of antibacterial property and antibacterial effect of antibacterial coatings (paint films)”, 10 mL of Escherichia coli ATCC 25922 bacterial suspension with a concentration of 5 x 10 5 CFU / mL is uniformly coated on the surface of the paint film of the test sample plate. After incubation at 37°C and 95% relative humidity for 24h, the antibacterial rate (%) is determined. According to this method, the antibacterial ability (%) of the test sample plate coating prepared by the mildew-resistant and antibacterial type nano water-based paint of examples 1-3 and comparative examples 1-9 is determined. The antibacterial ability (%) of the test sample plate coating after wet heat aging (80°C, 95% humidity, 1000h) is also determined to reflect the long-term effectiveness (%) of the coating. The test results are shown in Table 1.
[0038] Determination of mildew resistance and long-term effectiveness: According to the standard GB / T 1741-2020 “Determination of mildew resistance of paint films”, 10 mL of Aspergillus niger ATCC 1644 bacterial suspension with a concentration of 5 x 10 5A spore / mL of Aspergillus niger ATCC 16404 bacterial suspension is uniformly coated on the paint film surface of the test sample, and after 28 days of culture at a temperature of 37℃ and a relative humidity of 95%, the mold area ratio (%) is determined to reflect the mold resistance, and the smaller the mold area ratio, the stronger the mold resistance. The mold resistance (%) of the test sample coating prepared by the mold-resistant and antibacterial type nano water-based paint prepared by the application examples 1-3 and the comparative examples 1-9 was determined according to this method. And the mold resistance (%) of the test sample coating after hygrothermal aging (80℃, humidity 95%, for 1000h) was determined by the same method to reflect the long-acting property of the coating, and the test results are shown in Table 1.
[0039] Determination of impact resistance: According to GB / T 20624.2-2006 “Color paints and varnishes-Rapid impact (impact resistance) test, Part 2: Falling dart test (small area dart) ”test standard, the impact resistance (kg·cm) of the test sample coating prepared by the mold-resistant and antibacterial type nano water-based paint prepared by the application examples 1-3 and the comparative examples 1-9 was determined by using a paint film impact tester (TCJ-II, Shanghai Leao Test Instrument Co., Ltd.) with a weight of 1kg. The test results are shown in Table 1.
[0040] Determination of yellowing resistance: According to GB / T 1766-2008 “Color paints and varnishes Rating method for paint film aging”standard, the color difference (ΔE) of the test sample coating prepared by the mold-resistant and antibacterial type nano water-based paint prepared by the application examples 1-3 and the comparative examples 1-9 before and after experiencing 0.76W / m2@340nm cyclic ultraviolet aging for 500h was determined to reflect the yellowing resistance of the coating, and the test results are shown in Table 1.
[0041] Determination of adhesion: According to GB / T9286-2021 “Color paints and varnishes Cross-hatch test”standard, the adhesion grade (divided into 0-5 levels, 0 level has the strongest adhesion, and 5 level has the worst adhesion) of the test sample coating prepared by the mold-resistant and antibacterial type nano water-based paint prepared by the application examples 1-3 and the comparative examples 1-9 was determined, and the test results are shown in Table 1.
[0042] Table 1: Performance test results of examples 1-3 and comparative examples 1-9
[0043] Data analysis: As can be seen from Table 1, the mildew-proof and antibacterial nano water-based coating prepared in the embodiment of the present invention has excellent adhesion, impact resistance, yellowing resistance, antibacterial and mildew-proof ability and long-term effectiveness.
[0044] The above is a detailed description of an embodiment of the present invention. However, the content described is only a preferred embodiment of the present invention and should not be considered to limit the scope of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A mildew-proof and antibacterial nano water-based paint, characterized in that: The invention comprises the following raw materials in parts by weight: 12-14 parts of deionized water, 1.8-2.1 parts of a composite antibacterial agent, 0.8-0.9 parts of a wetting and dispersing agent, 0.1-0.12 parts of 2-hydroxy-4-n-octyloxybenzophenone, 55-60 parts of a waterborne polyurethane resin, and 1.5-1.8 parts of alcohol ester-12.
2. The mildew-proof and antibacterial nano water-based paint according to claim 1, characterized in that: The preparation method of the composite antibacterial agent is as follows: The composite nanoparticles were dissolved in deionized water and ultrasonically dispersed for 30-35 minutes. The modified metal particle dispersion was then added dropwise while stirring. After stirring for 1.8-2 hours, the silver nitrate solution was added dropwise. The mixture was stirred in the dark for 1.8-2 hours and then centrifuged. The precipitate was redissolved in another portion of deionized water and a light stabilizer 770 ethanol solution was added. Finally, the graphene oxide dispersion was added dropwise and the pH was adjusted to 7.7-7.
9. After stirring for 10-12 hours, the mixture was filtered and dried to obtain a composite antibacterial agent.
3. The mildew-proof and antibacterial nano water-based paint according to claim 2, characterized in that: The ratio of the composite nanoparticles, deionized water, modified metal particle dispersion, silver nitrate solution, another portion of deionized water, light stabilizer 770 ethanol solution, and graphene oxide dispersion is 1.0-1.2 g: 100-120 mL: 50-60 mL: 10-12 mL: 50-60 mL: 5-6 mL: 50-60 mL; The concentration of the silver nitrate solution is 0.08-0.1 mol / L; The mass fraction of the light stabilizer 770 ethanol solution is 4%.
4. The mildew-proof and antibacterial nano water-based paint according to claim 2, characterized in that: The preparation method of the composite nanoparticles is as follows: Chitosan is added to acetic acid-sodium acetate buffer and stirred at 40-45° C. for 2-3 hours. Dopamine hydrochloride, ascorbic acid and ammonium persulfate are then added and stirred in the dark for 24-25 hours. After dialysis for 48-50 hours, the precipitate is filtered and washed, centrifuged and freeze-dried to obtain composite nanoparticles.
5. The mildew-proof and antibacterial nano water-based paint according to claim 4, characterized in that: The usage ratio of the acetic acid-sodium acetate buffer, chitosan, dopamine hydrochloride, ascorbic acid, and ammonium persulfate is 100-120 mL: 2-2.4 g: 1.8-2 g: 0.1-0.12 g: 2.2-2.4 g; The concentration of the acetic acid-sodium acetate buffer solution is 0.5 mol / L, and the pH is 5.
0.
6. The mildew-proof and antibacterial nano water-based paint according to claim 2, characterized in that: The preparation method of the modified metal particle dispersion is as follows: A1: Dissolve cobalt nitrate hexahydrate in deionized water, then add tungsten phosphate precursor salt and heat to 80-85°C with stirring, then stir for 80-90 minutes. Cool to 25-30°C, add potassium chloride and stir for 15-20 minutes. Filter and wash, then dissolve the precipitate in deionized water at 80-90°C, cool at 3-5°C for 12-15 hours, filter, and finally vacuum dry the precipitate to obtain modified metal particles. A2: Add modified metal particles to deionized water, perform ultrasonic dispersion for 20-30 minutes, adjust the pH to 7.0 with ammonia water, add silane coupling agent KH550 after high-pressure homogenization, and stir at 58-60°C for 25-30 minutes to obtain a modified metal particle dispersion.
7. The mildew-proof and antibacterial nano water-based paint according to claim 6, characterized in that: The usage ratio of the cobalt nitrate hexahydrate, deionized water, tungsten phosphate precursor salt, potassium chloride, and deionized water at 80-90° C. in A1 is 0.41-0.49 g: 15-18 mL: 2.0-2.4 g: 5-6 g: 10-15 mL; The tungsten phosphate precursor salt in A1 is any one of sodium phosphotungstate and ammonium phosphotungstate; The usage ratio of deionized water, modified metal particles, and silane coupling agent KH550 in A2 is 50-60 mL: 0.5-0.6 g: 0.1-0.12 g; The pressure during the high-pressure homogenization in A2 is 110-120 MPa, and the number of high-pressure homogenization times is 3-5 times.
8. The mildew-proof and antibacterial nano water-based paint according to claim 2, characterized in that: The preparation method of the graphene oxide dispersion is as follows: Graphene oxide and dopamine are added to deionized water and ultrasonic treatment is performed for 25-30 minutes. Then, polyacrylic acid and nano-titanium dioxide are added and ultrasonic treatment is performed for 2-2.5 hours to obtain a graphene oxide dispersion.
9. The mildew-proof and antibacterial nano water-based paint according to claim 8, characterized in that: The usage ratio of the deionized water, graphene oxide, dopamine, polyacrylic acid and nano-titanium dioxide is 50-60 mL: 0.5-0.6 g: 0.03-0.05 g: 0.05-0.06 g: 0.2-0.24 g.
10. A process for preparing the mildew-proof and antibacterial nano water-based coating according to any one of claims 1 to 9, characterized in that: The following steps are involved: A composite antibacterial agent, a wetting dispersant, and 2-hydroxy-4-n-octyloxybenzophenone were added to deionized water and ultrasonically dispersed for 15 minutes. Then, a water-based polyurethane resin was added dropwise while stirring. After repeating high-speed shearing 3-4 times and adding alcohol ester-12, the pH was adjusted to 8.1-8.3 and high-speed shearing was performed again to obtain an anti-mildew and antibacterial nano water-based coating.